Reversible moisture damage in asphalt mixture - Muhammad, Arfat; Yaacob, Haryati; Hassan, N. A; Warid, M. N. M; Idham, M. K.; Ismail, Che Ros; Nor, H.M.; Hainin, Mohd Rosli; Mohamed, A.; Mashros, Nordiana; Yunus, N. Z. M; Hassan, S. A; et al. (2019)
A moisture damage has been one of the major concerns for HMA pavement by loss of adhesion between bitumen and aggregate surface or loss of the cohesion within asphalt binder due to action of water. Water is the one of major contributor towards the damage of asphalt pavement. The aim of this research is to evaluate the effects of Moisture Damage (MD) towards the performance of asphalt mixture under different conditions (dry, wet and dry back). For this research laboratory fabricated specimens were conditioned in accordance to ASTM D4867 to achieve desire saturation level up to 80% and then immersed in water for different soaking period to simulate flooding scenario. Indirect Tensile strength (ITS) and Resilient Modulus (RM) tests were performed on moisture conditioned specimens at regular interval (1,3 and 5 days). After 5 days testing specimens were stored at room temperature for another 5 days to dry and were tested again to determine the recoverability of moisture damage. The results from this study indicated that tensile strength and modulus gradually decreased with the increasing of conditioning period, and upon drying at certain period specimens recovered 82% and 76% of initial ITS and RM respectively. The results suggested that moisture damage in asphalt mixture tested is reversible.